2016
DOI: 10.3847/0067-0049/227/1/9
|View full text |Cite
|
Sign up to set email alerts
|

HERUS: A CO ATLAS FROM SPIRE SPECTROSCOPY OF LOCAL ULIRGs

Abstract: We present the Herschel SPIRE Fourier Transform Spectroscopy (FTS) atlas for a complete flux-limited sample of local ultraluminous infrared galaxies (ULIRGs) as part of the HERschel Ultra Luminous InfraRed Galaxy Survey (HERUS). The data reduction is described in detail and was optimized for faint FTS sources ,with particular care being taken for the subtraction of the background, which dominates the continuum shape of the spectra. To improve the final spectra, special treatment in the data reduction has been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 79 publications
1
32
0
Order By: Relevance
“…Photometry of the HERUS galaxies in the SPIRE bands PSW (250µm), PMW (350µm), PLW (500µm). These fluxes originally appeared in Pearson et al (2016) ters of our model are thus A, β and T. We fit these to the data for each individual HERUS ULIRG using the emcee Markov Chain Monte Carlo package 1 (Foreman-Mackey et al, 2013, for the general approach see also Lewis & Bridle 2002, Jaynes 2003 to probe the parameter space, equivalent to an exploration of the χ 2 surface with a nonlinear parameterization. We apply the following priors for our parameter values: for temperature (T) we adopt a uniform prior between 3 and 100K; for emissivity (β) we adopt a uniform prior between 0 and 3; for A, because the wide range of distances for our sources implies a range of amplitudes covering several orders 1 http://dan.iel.fm/emcee/current/ of magnitude, we adopt a uniform prior on log(A) between -3 and 10.…”
Section: Fitting Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Photometry of the HERUS galaxies in the SPIRE bands PSW (250µm), PMW (350µm), PLW (500µm). These fluxes originally appeared in Pearson et al (2016) ters of our model are thus A, β and T. We fit these to the data for each individual HERUS ULIRG using the emcee Markov Chain Monte Carlo package 1 (Foreman-Mackey et al, 2013, for the general approach see also Lewis & Bridle 2002, Jaynes 2003 to probe the parameter space, equivalent to an exploration of the χ 2 surface with a nonlinear parameterization. We apply the following priors for our parameter values: for temperature (T) we adopt a uniform prior between 3 and 100K; for emissivity (β) we adopt a uniform prior between 0 and 3; for A, because the wide range of distances for our sources implies a range of amplitudes covering several orders 1 http://dan.iel.fm/emcee/current/ of magnitude, we adopt a uniform prior on log(A) between -3 and 10.…”
Section: Fitting Methodsmentioning
confidence: 99%
“…Other observations for this sample are also available at a range of resolutions and wavelengths. For more details on the SPIRE spectroscopic observations see Pearson et al (2016).…”
Section: The Herus Samplementioning
confidence: 99%
“…We note, however, that there are examples of radio-quiet galaxies with jet-like winds indicating the existence of either a faint ongoing jet or a past jet event (e.g., Aalto et al 2016;Fernández-Ontiveros et al 2019). Finally, the CO spectral line energy distribution (SLED) up to J = 11 reveals highly excited gas in IRAS F08572+3915 (Papadopoulos et al 2010;Pearson et al 2016). While the strong AGN and starburst activity contribute significantly to the high molecular gas excitation, we cannot rule out that shocks resulting from a potential jet-dense ISM play a role in shaping the SLED beyond J ≈ 7 (e.g., Papadopoulos et al 2008;Pellegrini et al 2013).…”
Section: The Origin Of the Fast Gas Blob ∼ 6 Kpc Away From The Galaxymentioning
confidence: 96%
“…To make a similar analysis, we referred to Pearson et al (2016), who observed the CO emission lines from J = 5-4 to J = 13-12 in 43 ULIRGs using the Herschel Space Observatory. Seven of their sample galaxies are included in our targets, namely, all of the AKARI targets and IRAS 00397−1312.…”
Section: Heating Mechanismmentioning
confidence: 99%